Exploring the potential of wild perennial grasses as a biomass source in semi-arid Mediterranean environments - Gulias, Javier; Melis, Rita; Scordia, Danilo; Cifre, Josep; Testa, Giorgio; Cosentino, Salvatore L.; Porqueddu, Claudio (Italian Journal of Agronomy, 2018)
In Mediterranean environments, few perennial grass species are available for cultivation in rainfed systems and marginal lands, where plants with excellent adaptation are required. The aim of the present work was to determine the potentiality of five native Mediterranean perennial grasses for lignocellulosic biomass production. Wild accessions of three hemicryptophytes (Ampelodesmos mauritanicus, Hyparrhenia hirta, and Piptatherum miliaceum) and two geophytes (Saccharum spontaneum ssp. aegyptiacum and Sorghum halepense) were collected at three Mediterranean sites (Sicily, Sardinia and Majorca), and their morphological, physiological, productivity and quality traits were evaluated in the field. The species differed in height, with S. spontaneum and A. mauritanicus being the tallest. The leaf mass ratio ranged from 0.23 to 1.0 g g–1 among species. Maximum net photosynthesis was measured in the C4 species S. spontaneum and S. halepense (26.6 and 23.8 mmol CO2 m–2 s–1, respectively). A. mauritanicus showed the lowest transpiration rate and the highest instantaneous water use efficiency (2.7 mmol H2O m–2 s–1 and 6.9 mmol CO2 mmol H2O–1, respectively). S. spontaneum was the most productive species, yielding more than 18 Mg DM ha–1 as a three-year average. The highest content of acid detergent lignin was found in P. miliaceum, while A. mauritanicus was the species richest in hemicellulose and cellulose and poorest in ash. S. spontaneum showed the highest moisture content at harvest. Overall, the studied species showed interesting morphological, physiological, productive and qualitative traits. Nevertheless, additional research is necessary to investigate their long-term performance under different management strategies.